Implementation of Innovation in Improved Governance Original Local Income in Makassar City - Pagarra, Firman; Ibrahim, Muh. Akmal; Sukri, Sukri; Hasniati, Hasniati (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
Local Original Income plays an important role in regional finances which is a benchmark in the implementation of real regional autonomy. In the governance of increasing local original income, local governments are required to produce innovation in governance. This study aims to analyze the implementation of innovation in the governance of increasing local original income in Makassar City. This study uses a descriptive qualitative approach with data collection methods, namely observation, in-depth interviews and documentation. The informants in this study are the authorized parties and are directly involved in the governance of increasing local original income in the Makassar city government. The results of the study indicate that the implementation of innovation in the governance of increasing local original income in Makassar City has not been implemented optimally. This is because there is no agreement in working hours between the Regional Revenue Agency and its partners, namely PT. Pos Indonesia in terms of the conformity of reporting land and building tax payment data. In addition, the rules or regulations that often change so that it takes time to determine regional regulations related to regional taxes and levies.